The City of Miliana, the cradle of scout movement in Algeria 1930-1962 - tounsi, Abdul Rahman (The Algerian Historical Journal, 2026)
The scout movement in Algeria started ln Miliana in 1930 through lbn khaldoun Group led at that time by two native sons of that historical City namely Mohammed Bouras and El Sadek El-foul who both realized that Algerian Muslims lack scout groups following the escample of other people and religions the movement did not remain restricted to Miliana since it was nation widely spread northwand and sour HW and thanks to the efforts. Of those two men amdtheir. Leading followers ll was actually the supply ll was provided the national movement and the revolution with militants freedom fighters etc IT is indisputably the school of militancy.